Metabolic regulation in model ascomycetes – adjusting similar genomes to different lifestyles. Issue 8 (August 2015) - Whiteway, Malcolm; Tebung, Walters A.; Choudhury, Baharul I.; Rodríguez-Ortiz, Roberto
Highlights S. cerevisiae and C. albicans have similar genomic constitutions, but very dissimilar lifestyles. These yeasts regulate their central metabolism by a variety of mechanisms – this control allows their similar genomes to generate different lifestyles. This regulatory rewiring was initially identified as changes in specific transcription factors; we now see rewiring in post-translational controls as well as changes to the various general transcriptional control complexes.